Mediation of job embeddedness and satisfaction in the relationship between task characteristics and turnover: a multilevel study in Portuguese hotels - Ferreira, A. I.; Martinez, L. F.; Lamelas, J. P.; Rodrigues, R. I. (International Journal of Contemporary Hospitality Management, 2017)
Purpose - Employees' turnover intention is a key problem that hotel managers face daily. This is partially explained by the inevitability of performing tasks with little significance and low identity. This study aims to understand how job embeddedness and job satisfaction could lessen the undesirable effect of task characteristics on turnover intentions. Design/methodology/approach - A sample of 525 employees operating in 46 Portuguese hotels was used in this study. The questionnaire included demographic variables and four reliable instruments used to measure job satisfaction, job characteristics, job embeddedness and turnover intentions. The study used a multilevel statistical approach considering both the individual and the hotel levels of analysis. Findings - Through multilevel statistics, the findings suggest that both at the individual level and the hotel level of analysis, job satisfaction and job embeddedness fully mediated the relationship between different task characteristics (significance and identity) and turnover intentions. Research limitations/implications - Despite a possible absence of common method variance, due to the confirmatory factor analysis, social desirability bias may exist because of the self-reported nature of the survey. Practical implications - Managers should increase the perceived costs of employees leaving the hotel by introducing training programs and plans for career development. Also, to increase job embeddedness, managers should also rethink the organizational dynamics of this industry. Originality/value - This research provides empirical evidence of the antecedents and mediators of employees' intentions to leave the hotel industry both at the individual and at the hotel level (multilevel approach).